Aplicação da norma IEC 61970 para padronização de dados e interoperabilidade de redes elétricas inteligentes - Moura Neto, Mário Barreto de (2014)
In the context of the current modernization process through which the electrical power systems go through, the concept of Smart Grids and their foundations serve as guidelines. In the search for interoperability, communication between heterogeneous systems has been the subject of constant and increasing developments. Under this scenario, the work presented in this dissertation focuses primarily on the study and application of the data model contained in the IEC 61970 series of standards, best known as the Common Information Model (CIM). With this purpose, the general aspects of the standard are exposed and assisted by the concepts of UML and XML, which are essential for a complete understanding of the model. Certain features of the CIM, as its extensibility and generality are emphasized, which qualify it as ideal data model for the establishment of interoperability. In order to exemplify the use of the model, a case study was performed which modeled an electrical distribution network in medium voltage so as to make it suitable for integration with a multi-agent system in a standardized format and, consequently, adequate to interoperability. The complete process of modeling an electrical network using the CIM is shown. Finally, the development of an interface is proposed as a mechanism that enables human intervention in the data flow between the integrated systems. The use of PHP with a MySQL database, are justified because of their suitability in various usage environments.